Enhancing heavy equipment engineering students' skills through hydraulic and pneumatic systems training at SMKN 1 Sungai Limau - Wagino Wagino; Nuzul Hidayat; Hendra Dani Saputra; Agus Baharudin; Rahmat Desman Koto; M. Sadly Firmansyah; Akmal Akmal; Herwin Herwin (Universitas Muhammadiyah Magelang, 2024)
In the era of globalization, proficient technical skills are essential, especially in the field of heavy equipment engineering which requires an understanding of hydraulic and pneumatic systems. SMKN 1 Sungai Limau faces the challenge of limited facilities in preparing students for the demands of this industry. This training program utilizes a Problem-Based Learning method for theory and Project-Based Learning for practical application. Before the training commenced, students underwent a pretest with an average score of 45, indicating a low initial understanding. Following the theoretical and hands-on practical sessions, the posttest results showed a significant improvement with an average score of 70, reflecting an increase in student comprehension and skills. This average increase of 25 points serves as concrete evidence that this training is effective in enhancing students' skills in hydraulic and pneumatic systems. However, improvements in facilities and collaboration with industry are needed to ensure the relevance and sustainability of this training.